THE PUBLICATION DEVELOPMENT OF SOCIAL PROTECTION AND CLIMATE CHANGE RESEARCH (Social Security Management Journal, 2024)
Social protection incorporates a variety of interventions, such as cash transfers, insurance mechanisms, and employment safeguards, designed to assist underprivileged households and enable them to cope effectively with various adversities resulting from climate change. Using datasets from the Scopus and Web of Science (WoS) databases, the current study seeks to examine publication trends on research on social protection and climate change. The software packages ScientoPy and VOSviewer are used to analyse the retrieved datasets. This study found that the number of papers on social protection and climate change published in Scopus and WoS since 2000 has increased substantially. The journal “Sustainability” has developed as a significant venue for disseminating research. The study’s findings demonstrated cooperation among researchers from various geographical regions, highlighting the significance of knowledge sharing and the advancement of global solutions. The top ten most used keywords in previous research are “climate change”, “adaptation”, “sustainability”, “welfare”, “animal welfare”, “food security”, “agriculture”, “resilience”, “sustainable development”, and “vulnerability”. The study outcomes provide significant implications for policymakers, researchers, or practitioners to guide decision-making or foster collaborations in social protection and climate change research.